2012
DOI: 10.5173/ceju.2012.01.art4
|View full text |Cite
|
Sign up to set email alerts
|

Renal function after nephron-sparing surgery for renal tumors

Abstract: Nephron sparing surgery (NSS) is a technique more frequently utilized in the case of surgical treatment of kidney tumor. The aim of the study is to assess renal function in patients treated with NSS for renal tumors. Twenty patients, after NSS performed for renal tumor, were included in the study. In each patient dynamic renal scintigraphy was performed before surgical treatment (test No. 1) and after a mean interval of 12 months after surgical procedure (test No. 2). In each test renographic curves were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…found in their study on twenty patients with NSS for renal tumor that only four patients had significant deterioration in renal function after comparing the mean GFR. [23] Costabel et al . in their study on 45 patients with NSS for solitary kidney tumor over 10 years found significantly lower calculated GFR after surgery with loss of renal mass and male gender.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…found in their study on twenty patients with NSS for renal tumor that only four patients had significant deterioration in renal function after comparing the mean GFR. [23] Costabel et al . in their study on 45 patients with NSS for solitary kidney tumor over 10 years found significantly lower calculated GFR after surgery with loss of renal mass and male gender.…”
Section: Discussionmentioning
confidence: 99%
“…All the patients received adjuvant chemotherapy for 0–34 weeks with vincristine, dactinomycin, and/or doxorubicin as when deemed necessary and other drugs after consultation with medical oncology department. Renal function status was assessed with Tc-99m DTPA scan prior to surgery and 3 months after bilateral NSS and at follow-up yearly, and the total glomerular filtration rate (GFR) was noted[23] [Table 2]. In the interval between the two surgeries, renal function assessment was made with serum creatinine level.…”
Section: Methodsmentioning
confidence: 99%